Effects of chlorogenic acid on antimicrobial, antivirulence, and anti-quorum sensing of carbapenem-resistant Klebsiella pneumoniae - Wang, Lingbo; Zhang, Yi; Liu, Yan; Xu, Mengxin; Yao, Zhuocheng; Zhang, Xiaodong; Sun, Yao; Zhou, Tieli; Shen, Mo (Frontiers in Microbiology, 2022)
The rise in infections caused by the hypervirulent carbapenem-resistant Klebsiella pneumoniae (hv-CRKP) is an emergent threat to public health. It is therefore vital that therapeutic strategies for infections caused by this pathogen be urgently to developed. We assessed the effects of chlorogenic acid (CA), a natural phenolic compound, on antibacterial, antivirulence, and anti-quorum sensing (QS) of hv-CRKP. Five CRKP strains showed varying degrees of resistance to antibacterial agents. All strains carried the blaKPC-2 gene, primarily carrying rmpA2, iucA, and peg-344. CA showed no effect on CRKP growth at the 1/2 minimum inhibitory concentration (MIC), 1/4 MIC, and 1/8 MIC, CA could reduce the production of extracellular protease and capsular polysaccharides, and improve the survival rate of larvae in Galleria mellonella (G. mellonella) infection model. By means of crystal violet staining and scanning electron microscopy experiments, we observed that CA can inhibit the formation of CRKP biofilm. On the quantitative real-time PCR analysis, the expression of the luxS, mrkA and wbbm genes in most CRKP strains appeared downregulated because of the CA treatment. Besides, CA significantly inhibited the effect of AI-2 activity of BB170. Our study suggests that CA can be an effective antimicrobial, antivirulent compound that can target QS in hv-CRKP infections, thus providing a new therapeutic direction for treating bacterial infections.